2006
DOI: 10.1111/j.1365-313x.2006.02859.x
|View full text |Cite
|
Sign up to set email alerts
|

DamID, a new tool for studying plant chromatin profiling in vivo, and its use to identify putative LHP1 target loci

Abstract: SummaryWe show here that the in vivo methylation-based tagging technique DamID (DNA adenine methyltransferase identification) can be used for studies of DNA-protein interactions or chromatin profiling in plants. We have demonstrated the feasibility, reproducibility and sensitivity of the method in Arabidopsis thaliana, using the well-known yeast GAL4 transcription factor, for which DNA-binding sites (UAS G ) were introduced into the plant genome. We monitored the methylation resulting from the activity of DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 42 publications
0
45
1
1
Order By: Relevance
“…Animal HP1 is a chromodomain protein that binds methylated H3K9 and is strongly associated with constitutive heterochromatin (Hediger and Gasser, 2006), although is not involved in Polycomb repression. However, Arabidopsis LHP1 does not appear to have a role in the maintenance of constitutive heterochromatin (Libault et al, 2005;Nakahigashi et al, 2005), and seems to be involved in the regulation of euchromatic genes, such as FLC, AP3, PI, AG and FT (Nakahigashi et al, 2005;Germann et al, 2006;Sung et al, 2006b;Turck et al, 2007). LHP1 specifically associates in vivo with genes marked by the trimethylation of H3K27, although it is not involved in this histone modification (Turck et al, 2007;Zhang et al, 2007b), suggesting that LHP1 might contribute to PcG-mediated silencing in a PRC1-like analogous manner.…”
Section: Maintenance Of Repressive Statesmentioning
confidence: 99%
See 2 more Smart Citations
“…Animal HP1 is a chromodomain protein that binds methylated H3K9 and is strongly associated with constitutive heterochromatin (Hediger and Gasser, 2006), although is not involved in Polycomb repression. However, Arabidopsis LHP1 does not appear to have a role in the maintenance of constitutive heterochromatin (Libault et al, 2005;Nakahigashi et al, 2005), and seems to be involved in the regulation of euchromatic genes, such as FLC, AP3, PI, AG and FT (Nakahigashi et al, 2005;Germann et al, 2006;Sung et al, 2006b;Turck et al, 2007). LHP1 specifically associates in vivo with genes marked by the trimethylation of H3K27, although it is not involved in this histone modification (Turck et al, 2007;Zhang et al, 2007b), suggesting that LHP1 might contribute to PcG-mediated silencing in a PRC1-like analogous manner.…”
Section: Maintenance Of Repressive Statesmentioning
confidence: 99%
“…The regulation of FLC expression and its stable repression in response to winter temperatures involves a number of chromatin remodeling processes that have become a model for epigenetic regulation of gene expression in plants (reviewed in Farrona et al, 2008). Moreover, chromatin remodeling processes are also involved in the negative control of FT, SOC1 or AGL19 genes during vegetative development and their expression upon flowering induction, reinforcing the role of chromatin dynamics in the control of flowering time (Piñeiro et al, 2003;Takada and Goto, 2003;Bouveret el al., 2006;Germann et al, 2006;Imauzumi and Kay, 2006).…”
Section: Chromatin Organization In the Control Of Flowering Time A Mmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because several other potential direct targets identified in this study (Samach et al 2000) could not be confirmed in analyses of co mutants (Wigge et al 2005), additional experiments are needed to demonstrate unambiguously that FT is directly regulated by CO. FT is known to be a direct target of FLOWERING LOCUS C (FLC) and SHORT VEGETATIVE PHASE (SVP), transcriptional repressors that mediate the effects of exposure to winterlike conditions or to more modest changes in ambient temperature (Helliwell et al 2006;Searle et al 2006;Lee et al 2007). In addition, chromatin modification appears to play an important role in preventing inappropriate FT expression (Piñeiro et al 2003;Takada and Goto 2003;Germann et al 2006;Turck et al 2007).…”
Section: Molecular Basis Of the External Coincidence Modelmentioning
confidence: 99%
“…In addition, chromatin modifications in the genomic regions of FT prevent inappropriate expression of this gene that acts as a floral switch (Piñeiro et al, 2003;Takada and Goto, 2003;Germann et al, 2006;Imaizumi and Kay, 2006;Turck et al, 2007).…”
Section: Spatial Control Of Photoperiodic Floweringmentioning
confidence: 99%